Muscular and functional changes following adenotonsillectomy in children. Issue 4 (April 2015) - Bueno, Dandara de A.; Grechi, Taís H.; Trawitzki, Luciana V.V.; Anselmo-Lima, Wilma T.; Felício, Cláudia M.; Valera, Fabiana C.P.
Abstract Background It is recognized that adenotonsillar hypertrophy leads to muscular and functional changes in face, and that adenotonsillectomy is associated to improvement in this condition. However, the ideal interval one should wait until this spontaneous recovery is not well defined, neither if this recovery is expected to be complete or partial. Objective To compare the muscular and functional changes in face of children prior and after adenotonsillectomy in a monthly evaluation. Methods 8 children aged from 4 to 6 years were prospectively studied. All patients underwent adenotonsillectomy, and were assessed before and monthly-after surgery up to 6 months, through the Protocol of Orofacial Myofunctional Evaluation with Scores (OMES). Results There was a progressive improvement in OMES score in all measured parameters, including the "mobility" and "posture" sub-tests; this improvement was significant at the first month after surgery. The sub-test "function" was not affected by surgery. Improvement continued from the first to the sixth month after surgery, although it was not significant between these two periods. Additionally, all parameters remained altered after the final evaluation at six months. There was a significant correlation between the improvement in "mobility" sub-test and in total score of OMES. Conclusion We observed a partial recovery in facial muscular and functional changes following adenotonsillectomy, particularly during the first month after surgery. This improvement was especially observed in the "mobility" and "posture" sub-tests. We conclude that waiting for a spontaneous muscular and functional facial recovery during the first month post-operatively seems reasonable. Nevertheless, after this period, if the patient fails to achieve recovery, it may be advised that this child should undergo myofunctional therapy.